Economic Load Dispatch Downside with Valve - Point Result Employing a Binary Bat Formula - Mallikrjuna Bestha; K. Harinath Reddy; O. Hemakeshavulu (International Journal of Electrical and Computer Engineering (IJECE), 2014)
This paper proposes application of BAT algorithm for solving economic load dispatch problem. BAT algorithmic rule is predicated on the localization characteristics of micro bats. The proposed approach has been examined and tested with the numerical results of economic load dispatch problems with three and five generating units with valve point loading without considering prohibited operating zones and ramp rate limits. The results of the projected BAT formula are compared with that of other techniques such as lambda iteration, GA, PSO, APSO, ABC and basic principle. For each the cases, the projected algorithmic program outperforms the answer reported for the existing algorithms. Additionally, the promising results show the hardiness, quick convergence and potency of the projected technique.DOI:http://dx.doi.org/10.11591/ijece.v4i1.4233